2013
DOI: 10.1371/journal.pone.0076227
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Fragmentation and Ecological Traits Influence the Prevalence of Avian Blood Parasites in a Tropical Rainforest Landscape

Abstract: In the tropical rainforests of northern Australia, we investigated the effects of habitat fragmentation and ecological parameters on the prevalence of blood-borne parasites (Plasmodium and Haemoproteus) in bird communities. Using mist-nets on forest edges and interiors, we sampled bird communities across six study sites: 3 large fragments (20–85 ha) and 3 continuous-forest sites. From 335 mist-net captures, we recorded 28 bird species and screened 299 bird samples with PCR to amplify and detect target DNA. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 48 publications
3
40
1
Order By: Relevance
“…While these findings differ from some continental studies (e.g. Wood et al 2007;Bonneaud et al 2009;Chasar et al 2009;Loiseau et al 2010), they are consistent with a recent Australian study that found no differences in Plasmodium prevalence across a range of avian species in forest edge and interior habitats (Laurance et al 2013). It was also interesting to note that the globally widespread P. elongatum was by far the most common malaria parasite encountered in silvereyes in this study (n = 20).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While these findings differ from some continental studies (e.g. Wood et al 2007;Bonneaud et al 2009;Chasar et al 2009;Loiseau et al 2010), they are consistent with a recent Australian study that found no differences in Plasmodium prevalence across a range of avian species in forest edge and interior habitats (Laurance et al 2013). It was also interesting to note that the globally widespread P. elongatum was by far the most common malaria parasite encountered in silvereyes in this study (n = 20).…”
Section: Discussionsupporting
confidence: 78%
“…For example, recent studies in Africa by Bonneaud et al (2009) and Loiseau et al (2010) found higher Plasmodium prevalence in birds inhabiting pristine forests, whereas Chasar et al (2009) revealed one parasite species was more abundant in disturbed sites and another more so in pristine sites. Ribeiro et al (2005) found higher prevalence rates in large versus small forest fragments in Brazil, while Laurance et al (2013) found no difference in prevalence rates between continuous forest and smaller fragments in Australia. The aforementioned authors and Sehgal (2010) suggested vector abundance and species composition, breeding ecology and specificity for certain Plasmodium lineages are likely driving prevalence differences.…”
Section: Introductionmentioning
confidence: 90%
“…The main vectors of the two considered parasite genera differ: Plasmodium spp. Although several studies have analyzed how avian haemosporidian richness and prevalence (that is, the number of different parasites, and the proportion of infected hosts, per locality) are linked to a number of forest traits, either directly (Chasar et al 2009, Laurance et al 2013, Hernández-Lara et al 2017 or through the study of their vectors (Reiter and LaPointe 2007, Abella-Medrano et al 2015, Gudex-Cross et al 2015, studies on how habitat loss and fragmentation may determine their natural dynamics are scarce and offer inconclusive results (Sebaio et al 2010, references reviewed in Sehgal 2015, Ferreira et al 2017). (Santiago-Alarcon et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have focused on avian blood parasites as a model system for host-parasite interactions in an evolutionary and ecological context [1][2][3][4][5]. The disease is prevalent in areas with a suitable ecology and ethology of invertebrate hosts, simuliid flies and culicoid midges [6].…”
Section: Introductionmentioning
confidence: 99%